2008
DOI: 10.1152/ajprenal.00200.2007
|View full text |Cite
|
Sign up to set email alerts
|

Effects of amiloride, benzamil, and alterations in extracellular Na+ on the rat afferent arteriole and its myogenic response

Abstract: Wang X, Takeya K, Aaronson PI, Loutzenhiser K, Loutzenhiser R. Effects of amiloride, benzamil, and alterations in extracellular Na ϩ on the rat afferent arteriole and its myogenic response.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

7
48
2

Year Published

2009
2009
2021
2021

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 40 publications
(57 citation statements)
references
References 38 publications
7
48
2
Order By: Relevance
“…Studies directly evaluating the blockade of ENaC currents routinely demonstrate that 1 mol/L of amiloride and benzamil block ENaC by Ϸ80% and 90% to 100%, respectively. Accordingly, we interpret the observations made by both our laboratory 3 and Guan et al 1 that, at 1 mol/L, neither benzamil nor amiloride inhibits the myogenic response of the afferent arteriole as suggesting that ENaC plays little if any role in myogenic signaling in this vessel.…”
Section: Role Of Epithelial Sodium Channels In the Renal Myogenic Ressupporting
confidence: 72%
See 1 more Smart Citation
“…Studies directly evaluating the blockade of ENaC currents routinely demonstrate that 1 mol/L of amiloride and benzamil block ENaC by Ϸ80% and 90% to 100%, respectively. Accordingly, we interpret the observations made by both our laboratory 3 and Guan et al 1 that, at 1 mol/L, neither benzamil nor amiloride inhibits the myogenic response of the afferent arteriole as suggesting that ENaC plays little if any role in myogenic signaling in this vessel.…”
Section: Role Of Epithelial Sodium Channels In the Renal Myogenic Ressupporting
confidence: 72%
“…3 We argue that much of the data in the 2 studies are, in fact, complementary. In Guan et al 1 and in our study, benzamil and amiloride did not inhibit the afferent arteriolar myogenic response at concentrations Յ1 mol/L.…”
Section: Role Of Epithelial Sodium Channels In the Renal Myogenic Resmentioning
confidence: 93%
“…We also observed that 10 mol/L of benzamil decreased the arteriolar diameter by Ϸ21% 1 compared with a Ϸ55% decline in hydronephrotic kidneys. 6 However, benzamil enhanced myogenic responses in hydronephrotic kidneys 6 and inhibited autoregulation in our study, 2 suggesting that inhibition of autoregulation by amiloride and benzamil acts upstream of membrane depolarization, consistent with the original finding. 4,5 The reasons for the discrepancies between our study 2 and that of Wang et al 6 are not clear.…”
supporting
confidence: 88%
“…Indeed, some similarities exist between our work and that of Wang et al 6 Superfusion with 1.0 mol/L of amiloride or benzamil did not inhibit autoregulation. We also observed that 10 mol/L of benzamil decreased the arteriolar diameter by Ϸ21% 1 compared with a Ϸ55% decline in hydronephrotic kidneys.…”
supporting
confidence: 87%
“…One intriguing explanation of the origin of the myogenic response is the involvement of a stretch-or tensioninduced membrane depolarization mediated by ENaC that may be part of a complex membrane mechanotransducer (12). It has been proposed that ENaC play a role in mechanotransduction events in a variety of organisms (12) and are essential elements in the renal myogenic response (16,21,22), although the available data for involvement in renal autoregulation are by no means conclusive (40). As new data emerge, the present model could be modified to include this alternative mechanism, which would replace the assumption of a pressure-dependent shift in the voltage dependency of calcium channels with a pressuredependent membrane depolarization driven by an increase in membrane sodium conductance.…”
Section: Model Limitations and Potential Extensionsmentioning
confidence: 99%